Problematika Lembaga Pemasyarakatan dalam Sistem Peradilan Terpadu - Hutabarat, Rugun Romaida (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2017)
Correctional criminal justice system be seen from the issue of crime system, the idea of coaching, over capacity, and the adverse effects of imprisonment. The new alternative of imprisonment to be important. This study uses normative. This paper will discuss the implementation of associated ideas correctional imprisonment in Indonesia current legislation and the future alternative accordance with the idea of humanity. The answer above problems: first, over capacity in prisons into correctional implications have not been the implementation of selective and limited idea. Second, in the future should give consideration criteria such as medical, family, professional or social considerations that force/urgent. Considering there are still many problems in the implementation of imprisonment, over capacity, not the realization of the idea of correctional, adverse effects of imprisonment and global criticisms, then alternative imprisonment integrating the idea of humanity, saving, rehabilitation and selective expected to realize the integrated criminal justice system. Keywords: policy, correctional ide, integrated criminal justice system